Roman Pollak w świetle korespondencji z Bogdanem Zakrzewskim - Lijewska, Elżbieta (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
The article presents an image of professor Roman Pollak based on a collection of letters from Bogdan Zakrzewski (from the Archive of the Polish Academy of Sciences in Poznan), Pollak’s letters to the former student of his (since 2013, held in the Special Archive of the Ossoliński National Institute) and the reminiscences of Barbara Zakrzewska (in particular, the ones not published before the fall of communism in Poland). The analysis of the subject material presents a portrait of the professor as a renowned teacher, a demanding and kind lecturer, an open-minded scientist passionate especially about the Polish-Italian relationships and a skilled organiser of academic life who remained independent under the communist regime. The article emphasises the importance of the correspondence between the two professors for understanding the history of early postwar and subsequent Polish studies in Poznan and Wrocław, the history of “Pamiętnik Literacki” (Literary Memoir) and other research of both scholars. It also underscores the value of the analysed letters for determining the fate of those who graduated from Polish studies in Poznań thanks to the fact that professor Pollak maintained contacts with them after their graduation and supported them later in life.